The contribution of monetary institutions to stability - Harold James (Aussenwirtschaft, 2017)
The modern development of a policy revolution in the late twentieth century that places monetary stability at the core of central banking functions has three roots: an academic discussion of the design of monetary policy institutions; the example of successful central banking practice; and the impact of policy spillovers in a world in which increased capital mobility shaped a new sort of globalization. The article examines the relative weight of these factors in building the modern conception of central banking, and how the three factors interact with each other. The problematical consequence of a globalization-induced change in approach is that the accidental success of modern monetary policy pushed a mode of thinking that made monetary policy central and left out traditionally central elements of central banking - in particular, financial supervision.
Keywords: 330